Every Man for Himself! Gender, Norms and Survival in Maritime Disasters - Mikael Elinder; Oscar Erixson (Research Institute of Industrial Economics (IFN), 2012)
Since the sinking of the Titanic, there has been a widespread belief that the social norm of women and children first gives women a survival advantage over men in maritime disasters, and that captains and crew give priority to passengers. We analyze a database of 18 maritime disasters spanning three centuries, covering the fate of over 15,000 individuals of more than 30 nationalities. Our results provide a new picture of maritime disasters. Women have a distinct survival disadvantage compared to men. Captains and crew survive at a significantly higher rate than passengers. We also find that the captain has the power to enforce normative behavior, that the gender gap in survival rates has declined, that women have a larger disadvantage in British shipwrecks, and that there seems to be no association between duration of a disaster and the impact of social norms. Taken together, our findings show that behavior in life-and-death situation is best captured by the expression Every man for himself.
Keywords: C70; D63; D81; J16; 330; Social Norms; Disaster; Women and children first; Mortality; High stakes; Schiffsunfall; Sterblichkeit; Geschlecht; Soziale Norm; Welt